Battery
By regulating the ratio of the surface area to thickness of the battery and the spherical degree of the silicon-based material, the problems of high thickness expansion and poor circulation stability caused by volume expansion during the cycle of the battery are solved, and a battery design with high energy density, low expansion and high circulation stability are achieved.
Patent Information
- Application Number
- CN202411972518.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
During the charging and discharging cycle, existing batteries have high thickness expansion rate and poor cycle stability due to volume expansion of silicon-based materials, making it difficult to take into account both thin thickness, energy density and cycle stability.
By regulating the ratio of the first surface area to thickness of the battery and the spherical morphology of the silicon-based material, the structure of the negative electrode sheet is optimized to ensure that the battery has a lower expansion rate and a higher cycle stability during the charging and discharging process.
The ultra-thin design of the battery is realized, which improves energy density, while reducing thickness expansion and improving cycle stability.
Smart Images

Figure CN119674172A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery. Background Art
[0002] As the functions of 3C products such as smartphones and tablets continue to increase, the requirements for battery life and size are becoming higher and higher. The pursuit of thinner size and higher energy density is an important development direction for the battery industry. In order to increase the energy density of batteries and reduce the size of batteries, the most common method is to use silicon-based materials with higher theoretical capacity to replace graphite materials. However, silicon-based materials will experience a large volume expansion (about 300%) during the battery charge and discharge cycle, which seriously affects the thickness expansion rate and cycle stability of the battery.
[0003] Therefore, it is very important to invent a battery with thin thickness, high energy density, low expansion rate and high cycle stability. Summary of the invention
[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a battery. The battery of the present invention can make the battery have a thinner thickness, higher energy density, lower thickness expansion rate and higher cycle stability by simultaneously regulating the ratio of the first surface area of the battery to the thickness of the battery and the sphericity of the silicon-based material in the negative electrode sheet.
[0005] The present invention provides a battery, the battery comprises a negative electrode sheet, the negative electrode sheet comprises a silicon-based material, the sphericity of the silicon-based material is 0.66-0.99; the ratio S / H of the area S of the first surface of the battery to the thickness H of the battery is 800-3000, and the unit of the area S of the first surface is mm 2 , the unit of the thickness H is mm, the first surface is the surface with the largest area among the six surfaces of the battery; the thickness H≤3.5 mm.
[0006] On the premise that the negative electrode sheet uses the silicon-based material as the negative electrode active material, by further regulating the ratio of the area of the first surface of the battery to the thickness of the battery, the energy density and cycle stability of the battery can be effectively improved. This is because: reducing the thickness of the battery means that in the same volume or area, the proportion of active materials increases, thereby increasing the energy density of the battery. However, when the thickness of the battery is too thin, it is not conducive to the cycle stability of the battery. The inventors found that increasing the area of the maximum surface of the battery helps to improve the cycle stability of the battery. This is because a larger battery area means that more active materials can participate in the charge and discharge reaction, which helps the stability of the battery. When the ratio of the area of the first surface of the battery to the thickness of the battery is within a suitable range, the energy density and cycle stability of the battery are taken into account. In addition, for winding type batteries, by regulating the ratio of the two, the number of folds of the core can be reduced, thereby reducing the stress concentration phenomenon at the arc of the core, improving the wetting performance of the electrolyte, and helping to improve the cycle expansion of the battery, so that the battery has a lower expansion rate and cycle stability.
[0007] On this basis, by further regulating the sphericity of silicon-based materials, the cycle stability and thickness expansion rate of the battery can be further improved. The main reason is that when the sphericity of silicon-based materials is within a specific range, the silicon-based materials can evenly disperse the pressure to the inside of the material when subjected to external pressure, avoiding particle breakage due to stress concentration, exposing the inner surface of the silicon-based materials to the electrolyte, resulting in repeated formation of SEI film, which is not conducive to cycle stability. And when the sphericity of silicon-based materials is within a specific range, the silicon-based materials can also have a relatively flat surface morphology, and the surface defects (convexities or concave) can be controlled, which is conducive to the attachment of SEI film to the surface of silicon-based materials, avoiding the repeated growth of SEI film caused by the shedding of SEI film; when the sphericity of silicon-based materials is large, for example, greater than 0.99, the surface of silicon-based materials is too smooth, which is not conducive to the attachment of SEI film.
[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0009] (1) The battery of the present invention is an ultra-thin battery with high energy density.
[0010] (2) The battery of the present invention has a lower thickness expansion rate and higher cycle stability.
[0011] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 FIG. 1 is a schematic diagram showing the dimensions of a battery in an embodiment of the present invention; wherein: Figure 1 (a) is the front view, Figure 1 (b) is a side view.
[0013] Figure 2 Shown is a scanning electron microscope (SEM) image of a silicon-based material in an example of the present invention.
[0014] Figure 3 Shown is a SEM image of the negative electrode sheet of the battery in Example 1 after 500 cycles.
[0015] Figure 4 Shown is a SEM image of the negative electrode sheet of the battery in Comparative Example 1 after 500 cycles. DETAILED DESCRIPTION
[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0017] The present invention provides a battery, which may include a negative electrode sheet. The negative electrode sheet may include a silicon-based material, and the sphericity of the silicon-based material may be 0.66-0.99, for example, 0.66, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 0.99. The ratio S / H of the area S of the first surface of the battery to the thickness H of the battery may be 800-3000 (for example, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900 or 3000), and the unit of the area S of the first surface is mm 2 , the unit of the thickness H of the battery is mm, the first surface is the surface with the largest area among the six surfaces of the battery; the thickness H of the battery is ≤3.5mm (for example, 3.5mm, 3.4mm, 3.3mm, 3.2mm, 3.1mm, 3mm, 2.9mm, 2.8mm, 2.7mm, 2.6mm or 2.5mm).
[0018] In the present invention, the area S of the first surface and the thickness H of the battery have the conventional meanings in the art. The battery has six surfaces, such as Figure 1 FIG. 1 is a schematic diagram showing the dimensions of a battery in an embodiment of the present invention; wherein: Figure 1 (a) is the front view, Figure 1 (b) is a side view. As can be seen from the figure, the length of the battery is L, the width is W, and the thickness is H. The plane where the length L and the width W are located is the surface with the largest area among the six surfaces of the battery, that is, the first surface. The area S of the first surface can be measured by the following method: measure the length and width of the battery with a measuring tool, and multiply the length by the width to obtain the area S of the first surface.
[0019] In the present invention, the sphericity of the silicon-based material can be tested by conventional methods in the art, for example, after disassembling the battery, taking out the negative electrode sheet, cleaning the negative electrode sheet with dimethyl carbonate (DMC) and drying it. Use an argon ion grinder to perform cross-section polishing on the negative electrode sheet along the thickness direction, and observe the cross-sectional morphology of the negative electrode sheet using a scanning electron microscope (SEM). In the backscattering mode, the white spherical particles are silicon-based material particles. Measure the lengths of the maximum and minimum cross-sectional diameters of the same silicon-based material particle, which are recorded as d1 and d2 respectively, and d1 / d2 is the sphericity of the silicon-based material particle. Select at least 30 silicon-based material particles for sphericity testing, and take the average value, which is the sphericity of the silicon-based material.
[0020] In one example, a ratio S / H of an area S of the first surface of the battery to a thickness H of the battery is 1500-2500.
[0021] In one example, the sphericity of the silicon-based material is 0.8-0.95.
[0022] In the present invention, the surface of the silicon-based material may have a concave portion. Figure 2 The figure shows a scanning electron microscope (SEM) image of a silicon-based material in an example of the present invention. It can be seen from the figure that the surface of the silicon-based material has depressions, and the number of depressions on the silicon-based material particles is greater than or equal to one.
[0023] Constructing depressions on the surface of silicon-based materials can increase the specific surface area of silicon-based materials, which is not only beneficial to the contact and infiltration between silicon-based materials and electrolytes; it can also strengthen the adhesion between silicon-based materials and various substances in the battery (such as conductive agents, adhesives, etc.), and transform the bonding method from point contact to surface contact. The presence of depressions can increase the active sites on the surface of silicon-based materials, enhance the adhesion of SEI film on the surface of silicon-based materials, and is beneficial to improving the cycle stability of batteries.
[0024] In the present invention, the number of the recessed portions may be 1-100, for example, 1, 2, 6, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100.
[0025] In one embodiment, the number of the recessed portions is 20-50.
[0026] In the present invention, the number of depressions refers to the average number of depressions on a single silicon-based material particle; that is, the average number of depressions on the surface of each silicon-based material particle is 1-100, and does not mean that all silicon-based material particles have depressions on their surfaces. The number of depressions can be obtained by conventional methods in the art, such as using SEM, selecting at least 10 silicon-based material particles in the electron microscope image, counting the number of depressions on each silicon-based material particle, multiplying by 2 and taking the average value, to obtain the number of depressions.
[0027] In the present invention, the diameter of the recessed portion may be 0.1 μm-5 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm. The depth of the recessed portion may be 0.01 μm-5 μm, for example, 0.01 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.
[0028] On the premise that the number of depressions is within a specific range, further regulating the diameter and depth of the depressions can improve the cycle stability of the battery and reduce the thickness expansion rate. The reason is that when the diameter and depth of the depressions are within a specific range, it is not only beneficial to the infiltration and storage of the electrolyte, but also beneficial to improving the bonding force between the surface of the silicon-based material and the SEI film, thereby improving the film formation stability of the SEI film on the surface of the silicon-based material; when the diameter of the depression is too large (for example, greater than 5 μm) and / or the depth is too deep (for example, greater than 5 μm), it may cause more serious damage to the surface of the silicon-based material, which may easily lead to serious rupture of the silicon-based material after cycling, aggravating the side reaction with the electrolyte, and is not conducive to improving the cycle stability of the battery; in addition, if the ruptured silicon-based material has sharp edges, it may pierce the diaphragm, causing the risk of internal short circuit. However, when the diameter of the depression is too small (for example, less than 0.1 μm) and / or the depth is too shallow (for example, less than 0.01 μm), the bonding force between the surface of the depression and the SEI film is insufficient. As the volume of the silicon-based material expands, the SEI film on its surface may fall off, resulting in repeated growth of the SEI film, which is not conducive to the thickness expansion rate and cycle stability of the battery.
[0029] In one example, the diameter of the recessed portion is 0.3 μm-3 μm, and the depth of the recessed portion is 0.2 μm-2 μm.
[0030] In the present invention, the diameter and depth of the recess have the conventional meanings in this field. When the figure formed by the edge of the recess on the surface of the silicon-based material is a "regular circle", the diameter of the recess is the diameter of the regular circle; and when the figure formed by the edge of the recess on the surface of the silicon-based material is a non-"regular circle", the diameter of the recess is the equivalent diameter of a circle with the same area as the irregular circle. The diameter of the recess can be obtained by testing by conventional methods in this field, such as SEM, selecting at least 20 recesses in the electron microscope image (recesses on the same silicon-based material or on different silicon-based materials), measuring and calculating the diameter of each recess, and taking the average value. The depth of the recess refers to the vertical distance from the lowest point in the recess to the surface of the silicon-based material. The depth of the depression can be tested by conventional methods in the art, such as SEM, and at least 20 depressions are selected in the electron microscope image (depressions on the same silicon-based material or depressions on different silicon-based materials), and the depth of each depression is measured to take an average value.
[0031] In the present invention, the silicon-based material may include at least one of elemental silicon, silicon carbon, silicon oxygen and silicon alloy.
[0032] In one example, the silicon-based material includes the silicon carbon. The silicon carbon may have a core-shell structure. The core of the core-shell structure includes a porous carbon matrix and silicon particles located in the pores inside the porous carbon matrix, and the shell of the core-shell structure includes a carbon material.
[0033] In the present invention, the average particle size of the silicon carbon may be 5 μm-20 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm. The average particle size of the silicon particles may be 0.1 nm-2000 nm, for example, 0.1 nm, 0.5 nm, 1 nm, 5 nm, 10 nm, 50 nm, 100 nm, 500 nm, 1000 nm or 2000 nm.
[0034] When the average particle size of silicon carbon and the average particle size of silicon particles are within a specific range, it is beneficial to improve the electrochemical performance of silicon-based materials. When the average particle size of silicon carbon and / or the average particle size of silicon particles are small, it means that it has a larger specific surface area. At this time, the contact area with the electrolyte is large, resulting in more active lithium consumption during the first week of charging, which is not conducive to improving the cycle stability of the battery. When the average particle size of silicon carbon and / or the average particle size of silicon particles is large, it means that the diffusion path of lithium ions inside the silicon-based material is longer, resulting in poor kinetic performance of the negative electrode sheet; in addition, a larger average particle size may result in large gaps between particles, a lower packing density of the material, and difficulty in obtaining a negative electrode sheet with a higher compaction density, resulting in a low volume energy density of the battery.
[0035] In one example, the average particle size of the silicon particles is 1 nm-50 nm.
[0036] In the present invention, the average particle size of the silicon carbon and the average particle size of the silicon particles can be tested by conventional methods in the art. The average particle size of the silicon carbon is measured, for example, by SEM, selecting at least 10 silicon carbon particles in the electron microscope image, measuring the particle size of each silicon carbon particle, and taking the average value. The average particle size of the silicon particles is measured, for example, by transmission electron microscopy (TEM), selecting at least 20 silicon particles in the electron microscope image, measuring the particle size of each silicon particle, and taking the average value.
[0037] In the present invention, the median particle size Dv50 of the silicon carbon can be 5μm-20μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm. The median particle size Dv50 of the silicon carbon can be obtained by conventional methods in the art, such as laser particle size analyzer. In the present invention, Dv50 is the particle size corresponding to the cumulative volume distribution of 50% after the particles are arranged from small to large.
[0038] In the present invention, the thickness of the shell may be 2nm-20nm, for example, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm.
[0039] In one example, the shell has a thickness of 5 nm-10 nm.
[0040] The shell on the surface of the silicon-carbon material can effectively prevent direct contact between silicon and the electrolyte, thereby reducing the occurrence of side reactions and improving the stability of the negative electrode. At the same time, it can also inhibit the agglomeration of silicon, avoid the failure of silicon-based materials caused by stress concentration, and improve the cycle stability of the battery. In addition, since silicon is a semiconductor, the conductivity of the porous carbon matrix is significantly reduced after being composited with silicon. The shell coated with carbon-containing materials on the surface helps to improve the overall conductivity of the silicon-carbon material, thereby improving the rate performance of the battery.
[0041] In the present invention, the thickness of the shell can be tested by conventional methods in the art, such as using TEM, randomly selecting at least 50 silicon-carbon particles, and selecting at least 3 sites on each silicon-carbon particle, measuring the thickness of the shell at each site, and taking the average value.
[0042] In the present invention, based on the total mass of the silicon carbon, the content of the porous carbon matrix can be 38%-58% (for example, 38%, 40%, 45%, 50% or 58%), the content of the silicon particles can be 40%-60% (for example, 40%, 45%, 50%, 55% or 60%), and the content of the carbon material can be 2%-5% (for example, 2%, 3%, 4% or 5%).
[0043] By regulating the content of each component in silicon carbon, it is beneficial to reduce the thickness expansion rate of the battery while increasing the battery energy density.
[0044] In the present invention, after the battery is cycled for 500 cycles at 45° C., with a charge and discharge cut-off voltage of 2.5V-4.3V, 2C charging and 0.7C discharging, the average thickness of the SEI film on the surface of the silicon-based material is 500nm-1000nm, for example, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm.
[0045] In one example, after the battery is cycled for 500 cycles at 45° C., with a charge and discharge cut-off voltage of 2.5V-4.3V, 2C charging, and 0.7C discharging, the average thickness of the SEI film on the surface of the silicon-based material is 700nm-900nm.
[0046] In the present invention, the average thickness of the SEI film on the surface of the silicon-based material can be tested by conventional methods in the art, such as using an argon ion grinder to cut the negative electrode sheet to obtain a cross-sectional slice of the negative electrode sheet, and then using a SEM (under backscattering mode) to photograph the cross-sectional morphology of the negative electrode sheet, selecting at least 5 silicon-based materials, and selecting at least 5 sites on each silicon-based material, measuring the thickness of the SEI film at each site, and taking the average value.
[0047] In the present invention, the specific surface area of the silicon carbon can be 0.1m2 / g-10m 2 / g, for example 0.1m 2 / g, 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g or 10m 2 / g. The pore volume of the silicon carbon can be 0.0005cm 3 / g-0.002cm 3 / g, for example, 0.0005cm 3 / g, 0.001cm 3 / g or 0.002cm 3 / g.
[0048] When the specific surface area and pore volume of silicon carbon meet a specific range, the negative electrode active material can have a higher gram capacity. At the same time, it can also reduce the contact between silicon carbon and the electrolyte and reduce the formation of SEI film, thereby improving the initial efficiency and capacity retention rate of the battery.
[0049] In the present invention, the specific surface area and pore volume of the silicon carbon can be measured by conventional methods in the art, such as by N2 isothermal adsorption and desorption measurement, combined with BET, NLDFT and other model fitting calculations.
[0050] In the present invention, the true density of the silicon carbon can be 1.5 g / cm 3 -2.4g / cm 3 , for example 1.5 g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 or 2.4g / cm 3 .
[0051] When the true density of silicon carbon is within a specific range, it can ensure that the negative electrode active material has a higher gram capacity. At the same time, it can also avoid the failure of the negative electrode active material due to excessive volume expansion of silicon. When the true density of silicon carbon is small (for example, less than 1.5g / cm 3 ), it indicates that there are still many pores in the silicon carbon, and silicon is not fully deposited inside the porous carbon matrix, resulting in a low gram capacity of silicon carbon; and when the true density of silicon carbon is large (for example, greater than 2.4 g / cm 3 ), indicating that the number of pore structures in silicon-carbon is small. When the battery is charged, the volume of silicon embedded with lithium expands. If the pore structure is not sufficient to support the volume expansion of silicon, the structure of the negative electrode active material will be destroyed, which is not conducive to the cycle stability of the battery.
[0052] In the present invention, the true density of silicon carbon can be measured by conventional methods in the art, such as by gas replacement method.
[0053] In the present invention, the difference between the mass content of silicon on the surface of the core and the mass content of silicon inside the core is ≤10%, for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%.
[0054] When the difference between the mass content of silicon on the surface of the core and the mass content of silicon inside it is within a specific range, it means that in the silicon-carbon material, silicon can be uniformly deposited in the pores of the porous carbon matrix, and there is no silicon agglomeration on the core surface of the silicon-carbon material. When silicon is uniformly dispersed in the pores of the porous carbon matrix, the stress generated by the expansion of silicon during the lithium insertion process can be uniformly dispersed to various parts of the silicon-carbon material, thereby avoiding particle breakage and failure due to excessive local stress. If silicon is enriched on the core surface of the silicon-carbon material, it will be detrimental to the overall electrochemical performance of the material. Compared with silicon deposited inside the porous carbon matrix, silicon enriched on the surface has strong crystallinity, and the reaction with lithium ions to form a silicon-lithium alloy is an irreversible process, which will cause the retention rate of the battery to decay too quickly in the later stage of the cycle. In addition, the particle size of the silicon on the surface increases after agglomeration, and the diffusion and migration path of lithium ions becomes longer, resulting in poor battery rate performance. Therefore, avoiding silicon enrichment on the core surface can effectively improve the overall performance of silicon-carbon.
[0055] In the present invention, the mass content of silicon on the surface of the core and the mass content of silicon inside the core can be tested by a scanning electron microscope-energy dispersive spectrometer (SEM-EDS) method. In the EDS point scanning mode, 5-10 points are selected inside and on the surface of the silicon carbon core, respectively, and the silicon content at each point is measured to take the average value. The "surface" and the "interior" have the conventional meanings in the art, and the "interior" refers to the non-"surface" area in the core.
[0056] In the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector. The negative electrode active coating may include at least one of a negative electrode active material, a negative electrode conductive agent and a negative electrode binder. The negative electrode active material includes the silicon-based material. The negative electrode active material may also include a carbon-based material, and the carbon-based material, for example, includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon and hard carbon. The negative electrode conductive agent may include a conductive agent conventionally used in the art, such as conductive carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes (including at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes) and carbon fibers. The negative electrode binder may include a binder conventionally used in the art, such as at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide.
[0057] In the present invention, based on the total mass of the negative electrode active coating, the content of the negative electrode active material can be 80-99.8 weight % (for example, 80, 82, 84, 86, 88, 90, 92, 94, 96, 98, 99 or 99.8 weight %), the content of the negative electrode conductor can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %), and the content of the negative electrode binder can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %).
[0058] In the present invention, the battery may further include a diaphragm. The diaphragm includes at least a substrate layer, and the substrate layer has polar groups. By introducing polar groups (such as carboxyl, hydroxyl, amino, etc.) into the substrate layer, the mechanical properties of the diaphragm can be enhanced, so that the diaphragm has a relatively strong overall strength while being relatively thin, thereby avoiding battery deformation caused by the diaphragm being too thin. In this case, the thickness of the battery can be effectively reduced, so that the battery has a higher volume energy density.
[0059] In the present invention, the term "polar group" has the conventional meaning in the art, and generally refers to a chemical group having a significant electric dipole moment in a molecule. Whether the substrate layer has a polar group can be tested by conventional methods in the art, such as infrared spectroscopy.
[0060] In one example, the polar group includes at least one of a hydroxyl group, a carboxyl group, and an amino group.
[0061] In the present invention, the thickness of the diaphragm can be 3μm-9μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or 9μm. When the thickness of the diaphragm is thin (for example, less than 3μm), even if the substrate layer contains polar groups, it is difficult to effectively improve the mechanical strength of the diaphragm, resulting in the diaphragm being easily punctured, which will deteriorate the self-discharge and storage performance of the battery. In addition, a too thin diaphragm is prone to poor interfacial adhesion with the negative electrode active coating, and the pole piece is prone to powdering.
[0062] In the present invention, the battery may further include an electrolyte. The electrolyte may include at least one of fluoroethylene carbonate (FEC), a sulfur-containing additive, and lithium difluorophosphate (LiPO2F2).
[0063] FEC, sulfur-containing additives and LiPO2F2 all contribute to the formation of negative electrode films. Among them, the SEI film formed by sulfur-containing additives mainly includes sulfur-containing organic matter such as CH3CH(OSO2Li). At this time, the SEI film has better elasticity. Combined with the specific structure of silicon-based materials, it is more conducive to the stable attachment of the SEI film to the surface of silicon-based materials, effectively avoiding the separation of the SEI film from the silicon-based material due to the large volume expansion caused by the insertion / extraction of lithium during the charge and discharge process.
[0064] In the present invention, the sulfur-containing additive may include sulfur-containing additives conventionally used in the art, for example, at least one of ethylene sulfite (ES), diethylene sulfate (DTD), 1,3-propylene glycol cyclic sulfate (PCS), 1,3-propane sultone (PS) and 1,3-propylene sultone (PST).
[0065] In the present invention, the mass content of the FEC in the electrolyte can be 5%-25%, for example, 5%, 10%, 15%, 20% or 25%. The mass content of the sulfur-containing additive in the electrolyte can be 0.1%-5%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%. The mass content of the LiPO2F2 in the electrolyte can be 0.1%-1%, for example, 0.1%, 0.5% or 1%.
[0066] In the present invention, the mass contents of FEC, the sulfur-containing additive and LiPO2F2 in the electrolyte can be measured by conventional methods in the art, such as gas chromatography-mass spectrometry.
[0067] In the present invention, other components in the electrolyte, such as organic solvents, additives, etc., can be added according to conventional methods in the art.
[0068] In the present invention, the ratio of the volume energy density of the battery to the thickness of the battery is ≥240, for example, 240, 245, 250, 255, 260, 265, 270, 275, 280, 285, 290, 295 or 300. The unit of the energy density is Wh / L, and the unit of the thickness is mm.
[0069] By further adjusting the ratio of the battery's energy density to its thickness, the battery can have a higher space utilization rate.
[0070] In the present invention, the battery further comprises a positive electrode sheet. The positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating on at least one side of the positive electrode current collector. The positive electrode active coating comprises a positive electrode active material, and the positive electrode active material may comprise at least one of lithium cobalt oxide (LCO), nickel cobalt manganese ternary material (NCM), nickel cobalt aluminum ternary material (NCA), nickel cobalt manganese aluminum quaternary material (NCMA), lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium vanadium phosphate (LVP), lithium manganese oxide (LMO), lithium nickel oxide, nickel manganese oxide binary material, lithium-rich manganese-based material and lithium iron manganese phosphate.
[0071] In one example, the positive electrode active material includes a first particle and a second particle. The first particle includes a chemical formula of Li a1 Ni b1 Co c1 Mn d1 M 1 e1 O2 substances, 0.8≤a1≤1.3, 0.8≤b1≤0.98, 0.02≤c1≤0.2, 0.01≤d1≤0.14, 0 <e1≤0.08,M 1 The first particles include at least one of Al, Zr, B, Y, Sr, W, Ti, Mg and Nb, and the first particles include single crystal particles. The second particles include a chemical formula of Li a2 Ni b2 Co c2 Mn d2 M 2 e2 O2 substances, 0.9≤a2≤1.3, 0.8≤b2≤0.98, 0.02≤c2≤0.3, 0.01≤d2≤0.12, 0 <e2≤0.1,M 2 The present invention comprises at least one of Al, Zr, B, Y, Sr, W, Ti, Mg and Nb, and the second particles comprise polycrystalline particles.
[0072] Single crystal particles have excellent structural stability due to the uniformity of their internal crystal structure and consistent grain orientation. The primary particle size of polycrystalline particles is small, which greatly shortens the Li +transmission distance, which is beneficial to Li + transmission, thereby improving the battery rate performance. Therefore, when single crystal particles and polycrystalline particles are mixed and used, they have better structural stability and rate performance. In addition, the side reaction activity between silicon and the electrolyte is strong under high temperature conditions, which will lead to a large volume expansion. When the positive electrode active material includes single crystal particles and polycrystalline particles, it has a lower discharge temperature rise. Lowering the temperature of the battery during charging and discharging can effectively inhibit the volume expansion of silicon, so that the battery has higher cycle performance and energy density. Therefore, when the positive electrode active material meets specific characteristics, it can be used in combination with the silicon-based material provided in the present invention to further improve the overall energy density and cycle performance of the battery.
[0073] The present invention also provides a method for preparing the silicon carbon, the method comprising the following steps:
[0074] S1: mixing the carbon source, the catalyst, the surfactant and the solvent uniformly, placing the mixture in a first reaction container, and performing a first reaction;
[0075] S2: taking out the reaction product obtained in step S1, and performing a first cleaning and a first drying;
[0076] S3: mixing the product obtained in step S2 with an alkaline substance and performing a first sintering;
[0077] S4: performing a first vapor deposition on the product obtained in step S3;
[0078] S5: subjecting the product obtained in step S4 to a second vapor deposition.
[0079] In the present invention, in step S1, the carbon source, for example, includes at least one of resorcinol, formaldehyde, phenol, urea and acrylic acid. The catalyst, for example, includes aqueous ammonia. The concentration of aqueous ammonia can be 1wt%-5wt% (for example, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%). The surfactant, for example, includes hexadecyltrimethylammonium bromide (CTAB). The solvent, for example, includes deionized water and / or ethanol.
[0080] In the present invention, only the mass ratio of the carbon source to the surfactant needs to be regulated, and the mass of other materials (such as the catalyst and the solvent) is not limited. The mass ratio of the carbon source to the surfactant can be 1:(0.2-10), for example, 1:0.2, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.
[0081] The mixing temperature may be 25° C.-45° C. The first reaction container may include an inner sleeve and an outer sleeve, the inner sleeve may include polytetrafluoroethylene, and the outer sleeve may include stainless steel. The first reaction temperature may be 80° C.-150° C., and the first reaction time may be 12 h-36 h.
[0082] The particle size of the silicon-carbon material can be regulated by controlling the concentration of the catalyst. The higher the catalyst concentration, the faster the nucleation rate, the more particles per unit volume, and the smaller the particle size.
[0083] In the present invention, before step S2, the reaction container may be rinsed with cold water to quickly cool it to room temperature.
[0084] In the present invention, in step S2, the solvent used in the first cleaning may be deionized water. The temperature of the first drying may be 35°C-50°C.
[0085] In the present invention, in step S3, the alkaline substance includes potassium hydroxide (KOH), for example. The mass ratio of the product obtained in step S2 to the alkaline substance can be 1:(0.5-5), for example, 1:0.5, 1:1, 1:2, 1:3, 1:4 or 1:5.
[0086] In the present invention, in step S3, the first sintering can be performed in a tubular furnace. The atmosphere of the first sintering is, for example, nitrogen. The first sintering can be completed in multiple steps, for example, in two steps. First, the temperature is increased to 400°C-600°C at a heating rate of 5°C / min-15°C / min, and the temperature is kept for 1h-4h; then, the temperature is increased to 700°C-900°C at a heating rate of 5°C / min-15°C / min, and the temperature is kept for 0.5h-3h.
[0087] Step S3 may also include: after the first sintering, cooling to room temperature, second washing the product and second drying at 50° C.-70° C. The second washing may include, for example, first washing the cooled product with dilute hydrochloric acid for 1 to 4 times, then washing it with deionized water for 1 to 4 times, and centrifuging and / or filtering.
[0088] In the present invention, in step S4, a silicon source is used in the first vapor deposition. The silicon source may include at least one of silane, dichlorosilane, trichlorosilane and tetrachlorosilane. The atmosphere of the first vapor deposition is an inert gas. The inert gas may include at least one of nitrogen, argon and helium. The time of the first vapor deposition may be 1h-5h, for example, 1h, 2h, 3h, 4h or 5h. The temperature of the first vapor deposition may be 400℃-600℃, for example, 400℃, 500℃ or 600℃. The heating rate of the first vapor deposition may be 5℃ / min-15℃ / min, for example, 5℃ / min, 10℃ / min or 15℃ / min.
[0089] In the present invention, in step S5, a carbon source is used in the second vapor deposition. The carbon source may include at least one of methane, ethylene and acetylene. The atmosphere of the second vapor deposition is an inert gas. The inert gas may include at least one of nitrogen, argon and helium. The time of the second vapor deposition may be 0.5h-1.5h, for example, 0.5h, 1h or 1.5h. The temperature of the second vapor deposition may be 400℃-800℃, for example, 400℃, 500℃, 600℃, 700℃ or 800℃.
[0090] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0091] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0092] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0093] Preparation Example
[0094] The following preparation examples are used to illustrate the silicon-based materials of the present invention.
[0095] Preparation Example 1
[0096] The silicon-based material was prepared as follows:
[0097] S1: 120 mL of deionized water, 40 mL of ethanol and 0.4 mL of ammonia solution (concentration of 5 wt%) were mixed at 35°C, CTAB was added, magnetic stirring was performed for 30 min, and then m-diphenol and formaldehyde solution (concentration of 35 wt%) were added respectively; wherein the molar ratio of CTAB to m-diphenol was 1:3, and the molar ratio of m-diphenol to formaldehyde solution calculated as formaldehyde was 1:1.5, and stirring was performed for 1 h; the mixed solution was poured into a polytetrafluoroethylene inner sleeve, the inner sleeve was placed in a stainless steel outer sleeve, the seal was tightened, and the mixture was placed in a 120°C forced air drying oven for reaction for 24 h; after the reaction was completed, the outer sleeve was rinsed with cold water and quickly cooled to room temperature.
[0098] S2: Take out the reaction product obtained in step S1, wash it with deionized water, and dry it in a 40° C. forced air drying oven to obtain phenolic resin microspheres.
[0099] S3: The above-mentioned phenolic resin microspheres and KOH are mixed evenly in a mass ratio of 1:2, put into a tubular furnace, and heated from room temperature to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere and kept warm for 2h; heated to 800°C at a heating rate of 10°C / min and kept warm for 1h; after cooling to room temperature, the product is taken out, washed twice with dilute hydrochloric acid (concentration of 0.5mol / L), and then washed twice with deionized water, centrifuged, filtered and dried at 50°C to obtain porous phenolic resin microspheres.
[0100] S4: placing the porous phenolic resin microspheres in a tube furnace, heating the temperature from room temperature to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, introducing a SiH4-N2 mixed gas with a flow rate of 60 sccm and a SiH4 volume content of 20%, and maintaining the temperature for 3 hours;
[0101] S5: Raise the temperature to 550°C again, introduce acetylene gas at a flow rate of 100 sccm, and keep the temperature for 1 hour.
[0102] Among them, the prepared silicon-carbon material has a core-shell structure, the core includes a porous carbon material matrix and silicon particles, and the shell includes a carbon material; the average particle size of the silicon-carbon material is 9.8μm, the average particle size of the silicon particles is 12nm, and the shell thickness is 7.5nm; in the silicon-carbon material, the mass content of the porous carbon matrix is 48.0%, the mass content of the silicon particles is 49.6%, and the mass content of the carbon material is 2.4%; there are 22 depressions on the surface of the silicon-carbon material, the diameter of the depressions is 0.4μm, and the depth is 0.3μm; the sphericity of the silicon-carbon material is 0.95.
[0103] Preparation Example 2
[0104] The silicon-based material was prepared as follows:
[0105] S1: 120 mL of deionized water, 40 mL of ethanol and 0.4 mL of ammonia solution (with a concentration of 8 wt%) were mixed at 35°C, CTAB was added, and magnetic stirring was performed for 30 min. Then, m-diphenol and formaldehyde solution (with a concentration of 35 wt%) were added respectively; wherein the molar ratio of CTAB to m-diphenol was 1:3, and the molar ratio of m-diphenol to formaldehyde solution calculated as formaldehyde was 1:1.5, and stirring was performed for 1 h. The mixed solution was poured into a polytetrafluoroethylene inner sleeve, and the inner sleeve was placed into a stainless steel outer sleeve, the seal was tightened, and the mixture was placed in a 130°C forced air drying oven for reaction for 25 h. After the reaction was completed, the outer sleeve was rinsed with cold water and quickly cooled to room temperature.
[0106] S2: Take out the reaction product obtained in step S1, wash it with deionized water, and dry it in a 40° C. forced air drying oven to obtain phenolic resin microspheres.
[0107] S3: The above-mentioned phenolic resin microspheres and KOH are mixed uniformly in a mass ratio of 1:2, put into a tubular furnace, and heated from room temperature to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere and kept warm for 2 hours; the temperature is then increased to 800°C at a heating rate of 10°C / min and kept warm for 1 hour; the product is taken out after cooling to room temperature, washed twice with dilute hydrochloric acid, and then washed twice with deionized water, centrifuged, filtered and dried at 50°C to obtain porous phenolic resin microspheres.
[0108] S4: placing the porous phenolic resin microspheres in a tube furnace, heating the temperature from room temperature to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, introducing a SiH4-N2 mixed gas with a flow rate of 60 sccm and a SiH4 volume content of 20%, and maintaining the temperature for 2 hours;
[0109] S5: Raise the temperature to 550°C again, introduce acetylene gas at a flow rate of 100 sccm, and keep the temperature for 1 hour.
[0110] Among them, the prepared silicon-carbon material has a core-shell structure, the core includes a porous carbon material matrix and silicon particles, and the shell includes a carbon material; the average particle size of the silicon-carbon material is 5.6μm, the average particle size of the silicon particles is 15nm, and the shell thickness is 6.9nm; in the silicon-carbon material, the mass content of the porous carbon matrix is 57.1%, the mass content of the silicon particles is 40.7%, and the mass content of the carbon material is 2.2%; there are 48 depressions on the surface of the silicon-carbon material, the diameter of the depressions is 0.7μm, and the depth is 0.5μm; the sphericity of the silicon-carbon material is 0.81.
[0111] Preparation Example 3
[0112] The silicon-based material was prepared as follows:
[0113] S1: 120 mL of deionized water, 40 mL of ethanol and 0.4 mL of ammonia solution (concentration of 2 wt%) were mixed at 35°C, CTAB was added, magnetic stirring was performed for 30 min, and then m-diphenol and formaldehyde solution (concentration of 35 wt%) were added respectively; wherein the molar ratio of CTAB to m-diphenol was 1:3, and the molar ratio of m-diphenol to formaldehyde solution calculated as formaldehyde was 1:1.5, and stirring was performed for 1 h; the mixed solution was poured into a polytetrafluoroethylene inner sleeve, the inner sleeve was placed in a stainless steel outer sleeve, the seal was tightened, and the mixture was placed in a 125°C forced air drying oven for reaction for 26 h; after the reaction was completed, the outer sleeve was rinsed with cold water and quickly cooled to room temperature.
[0114] S2: Take out the reaction product obtained in step S1, wash it with deionized water, and dry it in a 40° C. forced air drying oven to obtain phenolic resin microspheres.
[0115] S3: The above-mentioned phenolic resin microspheres and KOH are mixed uniformly in a mass ratio of 1:2, put into a tubular furnace, and heated from room temperature to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere and kept warm for 2 hours; the temperature is then increased to 800°C at a heating rate of 10°C / min and kept warm for 1 hour; the product is taken out after cooling to room temperature, washed twice with dilute hydrochloric acid, and then washed twice with deionized water, centrifuged, filtered and dried at 50°C to obtain porous phenolic resin microspheres.
[0116] S4: placing the porous phenolic resin microspheres in a tube furnace, heating the temperature from room temperature to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, introducing a SiH4-N2 mixed gas with a flow rate of 60 sccm and a SiH4 volume content of 20%, and maintaining the temperature for 4 hours;
[0117] S5: Raise the temperature to 550°C again, introduce acetylene gas at a flow rate of 100 sccm, and keep the temperature for 1 hour.
[0118] Among them, the prepared silicon-carbon material has a core-shell structure, the core includes a porous carbon material matrix and silicon particles, and the shell includes a carbon material; the average particle size of the silicon-carbon material is 14.7μm, the average particle size of the silicon particles is 20nm, and the shell thickness is 9.6nm; in the silicon-carbon material, the mass content of the porous carbon matrix is 39.1%, the mass content of the silicon particles is 58.3%, and the mass content of the carbon material is 2.6%; there are 36 depressions on the surface of the silicon-carbon material, the diameter of the depressions is 1.1μm, and the depth is 0.7μm; the sphericity of the silicon-carbon material is 0.87.
[0119] Preparation Example 4
[0120] Used to verify the impact of "whether there are depressions on the surface of silicon-carbon materials".
[0121] The preparation was carried out in accordance with Preparation Example 1, except that the temperature in the blast drying oven in step S1 was changed to make the surface of the silicon-carbon material free of depressions (by adjusting the temperature, the presence or absence of depressions on the surface of the resin microspheres and the number of depressions can be controlled. When the temperature is high, some functional groups on the surface of the resin microspheres decompose, resulting in collapse and formation of depressions), as follows:
[0122] The temperature in the blast drying oven in step S1 was adjusted from 120°C to 90°C; and the ratio of the amount of CTAB to m-diphenol was adjusted to 1:4 (the sphericity of the silicon-carbon material was controlled to be 0.95 by adjusting the ratio of the amount of the two); the other parameters were consistent with those in Preparation Example 1. The surface of the silicon-carbon material had no depressions, and the sphericity of the silicon-carbon material was 0.95.
[0123] Preparation Example 5
[0124] This group of preparation examples is used to verify the impact of changes in the number of "depressions".
[0125] This group of preparation examples was carried out with reference to Preparation Example 1, except that the number of the depressed portions was regulated by changing the temperature of the blast drying oven in step S1, as follows:
[0126] Preparation Example 5a
[0127] The temperature in the blast drying oven in step S1 was adjusted from 120°C to 100°C, and the other parameters were consistent with those in Preparation Example 1. The number of the recessed portions was 6, the diameter was 0.4 μm, and the depth was 0.2 μm; and the sphericity of the silicon-carbon material was 0.98.
[0128] Preparation Example 5b
[0129] The temperature in the blast drying oven in step S1 was adjusted from 120°C to 150°C, and the other parameters were consistent with those in Preparation Example 1. The number of the recessed portions was 88, the diameter was 0.5 μm, and the depth was 0.3 μm; and the sphericity of the silicon-carbon material was 0.68.
[0130] Preparation Example 6
[0131] Used to verify the impact of changes in the "diameter and depth of the recessed portion".
[0132] The preparation was carried out in accordance with Preparation Example 1, except that the diameter and depth of the depressed portion were adjusted by changing the time of being placed in the blast drying oven in step S1, as follows:
[0133] The reaction time in the blast drying oven in step S1 was adjusted from 24 hours to 28 hours, and the other parameters were consistent with those in Preparation Example 1. The number of the recessed portions was 24, the diameter was 2.7 μm, and the depth was 1.6 μm; and the sphericity of the silicon-carbon material was 0.84.
[0134] The silicon-carbon materials prepared in the above preparation examples all meet the following requirements: the specific surface area is 0.1 m 2 / g-10m 2 / g; pore volume is 0.0005cm 3 / g-0.002cm 3 / g; true density is 1.5g / cm 3 -2.4g / cm 3 ; The difference between the mass content of silicon on the core surface of the silicon-carbon material and the mass content of silicon inside the core is ≤10%.
[0135] Comparative Preparation Example
[0136] The silicon-based material was prepared as follows:
[0137] Petroleum coke and KOH are mixed uniformly in a mass ratio of 1:2, placed in a porcelain boat and put into a tubular furnace, and heated from room temperature to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere, and kept warm for 2 hours, then cooled to room temperature, and the above product is washed twice with dilute hydrochloric acid (concentration of 0.5 mol / L), and then washed twice with deionized water, centrifuged, filtered and dried to obtain a block porous activated carbon material; the above block porous activated carbon material is placed in a tubular furnace, and heated from room temperature to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, and a SiH4-N2 mixed gas with a flow rate of 60sccm and a SiH4 volume content of 20% is introduced, and maintained for 3 hours; then the temperature is raised to 700°C, and acetylene gas with a flow rate of 100sccm is introduced, and kept warm for 1 hour.
[0138] The prepared silicon-carbon material has a core-shell structure, wherein the core comprises a porous carbon material matrix and silicon particles, and the shell comprises a carbon material; the average particle size of the silicon-carbon material is 9.6 μm, and the sphericity of the silicon-carbon material is 0.42.
[0139] The following examples are provided to illustrate the batteries of the present invention.
[0140] Example 1
[0141] Prepare the battery as follows:
[0142] (1) Preparation of negative electrode sheet
[0143] The negative electrode active material (the silicon-carbon material prepared in Preparation Example 1 and artificial graphite are mixed in a mass ratio of 2:8), sodium carboxymethyl cellulose, styrene-butadiene rubber, carbon black and single-walled carbon nanotubes are mixed in a mass ratio of 85:2:5.5:7:0.5, deionized water is added, and the mixture is mixed in a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a copper foil, placed in an oven, dried at 80°C, and rolled and cut to obtain a negative electrode sheet.
[0144] (2) Preparation of positive electrode
[0145] The positive electrode active material (including a first particle and a second particle, wherein the first particle is a LiNi 0.9 Co 0.04 Mn 0.04 Al 0.02 O2 is a single crystal particle; the second particle is a LiNi 0.85 Co 0.08 Mn 0.04 Al 0.03 O2 material, which is polycrystalline particles; the mass ratio of the first particle to the second particle is 85:15), polyvinylidene fluoride, acetylene black and single-walled carbon nanotubes are evenly mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone is added, and the mixture is evenly mixed under the action of a vacuum stirrer to obtain a positive electrode slurry, the positive electrode slurry is evenly coated on an aluminum foil, put into an oven, and dried at 120°C. After rolling and slitting, a positive electrode sheet is obtained.
[0146] (3) Preparation of electrolyte
[0147] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and propyl propionate are mixed in a mass ratio of 1:1:8 to form an organic solvent; 14% of lithium hexafluorophosphate, 15% of FEC, 3% of PS and 0.5% of LiPO2F2 based on the total mass of the electrolyte are added to the above organic solvent, stirred evenly, and after passing the moisture and free acid tests, an electrolyte is obtained.
[0148] (4) Preparation of batteries
[0149] The negative electrode sheet, the separator (thickness of 7 μm, the substrate layer is modified polyethylene, having polar groups of carboxyl, hydroxyl and amino) prepared in step (1) and the positive electrode sheet prepared in step (2) are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet; a battery is obtained through the processes of winding, packaging, injecting the electrolyte prepared in step (3), secondary sealing, formation, sorting and the like;
[0150] Among them, the area S of the first surface of the battery is 6254mm 2, the thickness H is 3.15 mm, and the ratio of the area of the first surface to the thickness S / H is 1985.
[0151] Example 2
[0152] The method is carried out in accordance with Example 1, except that the area S of the first surface of the battery, the thickness H of the battery and the composition of the electrolyte are changed as follows: the area S of the first surface of the battery is 4673 mm 2 , the thickness H is 3.08 mm, and the ratio of the area of the first surface to the thickness S / H is 1517; the mass content of FEC in the electrolyte is 13.4%, the mass content of PS is 3.7%, and the mass content of LiPO2F2 is 0.72%.
[0153] Example 3
[0154] The method is carried out in accordance with Example 1, except that the area S of the first surface of the battery, the thickness H of the battery and the composition of the electrolyte are changed, as follows: the area S of the first surface of the battery is 7081 mm 2 , the thickness H is 2.86 mm, and the ratio of the area of the first surface to the thickness S / H is 2476; the mass content of FEC in the electrolyte is 18.7%, the mass content of PS is 2.4%, and the mass content of LiPO2F2 is 0.25%.
[0155] Example 4 Group
[0156] This group of embodiments is used to verify the impact of changes in "silicon-based materials".
[0157] This group of examples is carried out with reference to Example 1, except that the silicon-based material prepared in Preparation Example 1 is adjusted as follows:
[0158] Example 4a, replacing the silicon-carbon material prepared in Preparation Example 1 with the silicon-carbon material prepared in Preparation Example 2 of the same mass;
[0159] In Example 4b, the silicon-carbon material prepared in Preparation Example 1 is replaced with the silicon-carbon material prepared in Preparation Example 3 of the same mass;
[0160] Example 4c, replacing the silicon-carbon material prepared in Preparation Example 1 with the silicon-carbon material prepared in Preparation Example 4 of the same mass;
[0161] Example 4d, replacing the silicon-carbon material prepared in Preparation Example 1 with the silicon-carbon material prepared in Preparation Example 5a of the same mass;
[0162] Example 4e, replacing the silicon-carbon material prepared in Preparation Example 1 with the silicon-carbon material prepared in Preparation Example 5b of the same mass;
[0163] In Example 4f, the silicon-carbon material prepared in Preparation Example 1 is replaced with the silicon-carbon material prepared in Preparation Example 6 of the same mass.
[0164] Example 5 Group
[0165] This group of embodiments is used to verify the influence of the change of "the ratio S / H of the first surface area to the thickness of the battery".
[0166] This group of examples is carried out with reference to Example 1, except that the ratio S / H of the first surface area to the thickness is adjusted by changing the area S of the first surface, as follows:
[0167] Example 5a, the area S of the first surface of the battery is 2568 mm 2 , the thickness H is 3.18 mm, and the ratio of the area of the first surface to the thickness S / H is 808;
[0168] Example 5b, the area S of the first surface of the battery is 9436 mm 2 , the thickness H is 3.16 mm, and the ratio of the area of the first surface to the thickness S / H is 2986.
[0169] Example 6
[0170] Used to verify the impact of changes in the polar groups in the base material layer of the separator.
[0171] The method is carried out with reference to Example 1, except that the composition of the substrate layer of the diaphragm is changed, and the thickness of the diaphragm is thickened (since the presence of polar groups can improve the mechanical strength of the diaphragm, when there are no polar groups in the substrate layer, the thickness of the diaphragm needs to be increased accordingly), as follows:
[0172] The base layer of the separator is a polyethylene film with a thickness of 8 μm; the thickness H is 3.41 mm, and the ratio of the area to the thickness of the first surface is 1834.
[0173] Comparative Example 1
[0174] The process was carried out in accordance with Example 1, except that the silicon-carbon material prepared in Preparation Example 1 was replaced by the silicon-carbon material prepared in the Comparative Preparation Example of the same mass.
[0175] Comparative Example 2
[0176] The method is carried out in accordance with Example 1, except that the area S of the first surface of the battery is changed as follows: the area S of the first surface of the battery is 2047 mm 2 , the thickness H is 3.21 mm, and the ratio of the area of the first surface to the thickness S / H is 654.
[0177] Comparative Example 3
[0178] The method is carried out in accordance with Example 1, except that the thickness H of the battery is changed as follows: the area S of the first surface of the battery is 6256 mm 2 , the thickness H is 4.2 mm, and the ratio of the area of the first surface to the thickness S / H is 1490.
[0179] Test Case
[0180] (1) Volume energy density test
[0181] The batteries prepared in the examples and comparative examples were tested for volume energy density, and the specific test method is as follows:
[0182] At room temperature (25°C), using the LAND test system:
[0183] 1- Charge at 0.5C constant current to 4.3V, charge at 0.02C constant voltage, and let stand for 10 minutes;
[0184] 2-Discharge at 0.2C to 2.5V, let stand for 10 minutes, and record the amount of electricity during the discharge process as E;
[0185] 3- Charge to 3.8V at 0.5C, and measure the thickness of the battery using a PPG thickness gauge, recorded as c;
[0186]
[0187] The volume energy density (VED) is calculated according to the above formula in units of Wh / L, where a, b, and c are the width, height, and thickness of the battery, respectively; the results are recorded in Table 1.
[0188] (2) Cycle test
[0189] The batteries prepared in the examples and comparative examples were subjected to cycle tests, and the specific test methods are as follows:
[0190] At high temperature (45°C), using the LAND test system:
[0191] 1- Charge at 2C constant current to 4.3V, charge at constant voltage to 0.1C, and let stand for 10 minutes;
[0192] 2-Discharge at 0.7C to 2.5V and let stand for 10 minutes;
[0193] The weekly capacity retention rate of the battery was calculated based on the initial discharge capacity and weekly discharge capacity of the battery; the initial thickness of the battery was tested and recorded using a PPG thickness gauge before the cycle began; the battery was fully charged after each 100 cycles, and the current thickness was tested using a PPG thickness gauge; the thickness change rate was calculated based on the initial thickness; after the battery cycled 500 times, a battery was disassembled to measure the thickness of the SEI film on the surface of the silicon-based material, and the results are recorded in Table 1. Figure 3 The figure shows the SEM image of the negative electrode sheet of the battery in Example 1 after 500 cycles. Figure 4 This is a SEM image of the negative electrode sheet of the battery in Comparative Example 1 after 500 cycles. It can be seen from the figure that the thickness of the SEI film on the surface of the silicon-carbon material in Example 1 is about 730nm, while the thickness of the SEI film on the surface of the silicon-carbon material in Comparative Example 1 is about 1100nm. The thickness of the SEI film on the surface of the silicon-carbon material in Example 1 is significantly less than that in Comparative Example 1. And compared with the blocky silicon-carbon material in Comparative Example 1, the silicon-carbon material in Example 1 can avoid protruding edges and corners, piercing the diaphragm, and causing self-discharge.
[0194] Table 1
[0195]
[0196]
[0197] It can be seen from Table 1 that the battery of the present invention, compared with the comparative example, can take into account thinner thickness, higher energy density, lower thickness expansion rate and higher cycle stability.
[0198] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A battery, characterized in that: The battery comprises a negative electrode sheet, the negative electrode sheet comprises a silicon-based material, and the sphericity of the silicon-based material is 0.66-0.99; The ratio S / H of the area S of the first surface of the battery to the thickness H of the battery is 800-3000, and the unit of the area S of the first surface is mm 2 , the unit of the thickness H is mm, the first surface is the surface with the largest area among the six surfaces of the battery; the thickness H≤3.5 mm.
2. The battery according to claim 1, wherein The ratio S / H of the area S of the first surface of the battery to the thickness H is 1500-2500; And / or, the sphericity of the silicon-based material is 0.8-0.
95.
3. The battery according to claim 1 or 2, wherein: The silicon-based material has a concave portion on its surface; Preferably, the number of the recessed portions is 1 to 100; more preferably, 20 to 50; Preferably, the depth of the recessed portion is 0.01 μm-5 μm; more preferably 0.2 μm-2 μm; Preferably, the diameter of the recessed portion is 0.1 μm-5 μm; more preferably 0.3 μm-3 μm.
4. The battery according to claim 1 or 2, wherein The silicon-based material includes at least one of elemental silicon, silicon carbon, silicon oxygen and silicon alloy; Preferably, the silicon-based material includes the silicon carbon.
5. The battery according to claim 4, wherein The silicon carbon comprises a core-shell structure; the core of the core-shell structure comprises a porous carbon matrix and silicon particles located in the internal pores of the porous carbon matrix, and the shell of the core-shell structure comprises a carbon material; Preferably, the average particle size of the silicon carbon is 5 μm-20 μm; Preferably, the average particle size of the silicon particles is 0.1nm-2000nm; more preferably 1nm-50nm; Preferably, the thickness of the shell is 2nm-20nm; more preferably 5nm-10nm.
6. The battery according to claim 1 or 2, wherein: When the battery is cycled for 500 cycles at 45° C., with a charge and discharge cut-off voltage of 2.5V-4.3V, 2C charging, and 0.7C discharging, the average thickness of the SEI film on the surface of the silicon-based material is 500nm-1000nm, preferably 700nm-900nm.
7. The battery according to claim 1 or 2, wherein: The battery further comprises a separator, which comprises at least a substrate layer; the substrate layer has polar groups; the thickness of the separator is 3 μm-9 μm; Preferably, the polar group includes at least one of a hydroxyl group, a carboxyl group and an amino group.
8. The battery according to claim 1 or 2, wherein: The battery further comprises an electrolyte, wherein the electrolyte comprises at least one of fluoroethylene carbonate, a sulfur-containing additive and lithium difluorophosphate; Preferably, the mass content of the fluoroethylene carbonate in the electrolyte is 5%-25%; Preferably, the mass content of the sulfur-containing additive in the electrolyte is 0.1%-5%; Preferably, the mass content of the lithium difluorophosphate in the electrolyte is 0.1%-1%.
9. The battery according to claim 1 or 2, wherein: The ratio of the volume energy density of the battery to the thickness H is ≥240; the unit of the volume energy density is Wh / L, and the unit of the thickness H is mm.
10. The battery according to claim 4, wherein The specific surface area of the silicon carbon is 0.1m 2 / g-10m 2 / g; And / or, the pore volume of the silicon carbon is 0.0005cm 3 / g-0.002cm 3 / g; And / or, the true density of the silicon carbon is 1.5 g / cm 3 -2.4g / cm 3 ; And / or, the difference between the mass content of silicon on the surface of the silicon-carbon core and the mass content of silicon inside the silicon-carbon core is ≤10%.
Citation Information
Cited By
Silicon-carbon composite negative electrode material and preparation method and application thereof
CN120933326A
Battery
WO2026145532A1